The shadows of total war : Europe, East Asia, and the United States, 1919-1939 - Chickering, Roger, 1942-; Förster, Stig (Publications of the German Historical Institute., 2003)
The essays in this compelling collection examine the period between the two world wars of the twentieth century; one of the most exciting in the history of war. They explore the lingering consequences of World War I; the intellectual efforts to analyze this conflict's military significance; the attempts to plan for another general war; and several episodes in the 1930s that portended the war that erupted in 1939.